DNA Sequencing by Recognition and Its Potential Application with Nanopore Sequencing - Liang, Feng; Zeng, Yan; Wang, Lei (Current Organic Chemistry, 2014)
Nanopore based DNA Sequencing by Recognition technique relies on the sense of current between a pair of electrodes, which span nanopore and trap DNA nucleotides. The electrodes typically are tips of scanning tunneling microscope (STM) functionalized with recognition molecules that can distinguish individual DNA bases through hydrogen bonds. This manuscript aims to provide a summary of current research progress of nanopore DNA sequencing, DNA Sequencing by Recognition, evolution of recognition molecules applied in Sequencing by Recognition, and discusses the opportunities and challenges in this rapidly growing field.
Keywords: tunneling